Формування компетентностей ІТ-фахівців при проектному навчанні у формі стартапу - Слюсарчук, Юрій; Слюсарчук, Ольга; Slyusarchuk, Yuriy; Slyusarchuk, Olga (Видавництво Львівської політехніки, 2018)
Пропонуються шляхи вирішення проблеми підвищення якості освіти бакалаврів ІТ-спеціальностей. Формування компетентностей майбутніх фахівців реалізується на основі технологій проектного навчання у формі стартапу. Оцінювання показників сформованості компетентностей при проектно-орієнтованому навчанні базується на Скрам-методології.

The ways of solving the problem of improving the quality of bacheloreducationin IT specialties are offered. Formation of competencies of future specialists is based on the technology of project-orientedstudy in the form of startup.Evaluation of competency formation indicatorsis made using scrum methodology.
Forming of IT-specialist competencies during project-oriented study in the form of startup
Keywords: проектно-орієнтоване навчання; компетенція; стартап; IT-фахівець; project-orientedstudy; competency; startup; IT specialist; 37.044.588